I greet you at the beginning of a great career the selected correspondence of Lawrence Ferlinghetti and Allen Ginsberg, 1955 - 1997 - Ferlinghetti, Lawrence 1919-2021 (City Lights, 2015)
"In 1969, Allen Ginsberg wrote to his friend, fellow poet, and publisher Lawrence Ferlinghetti, "Alas, telephone destroys letters!" Fortunately, however, by then the two had already exchanged a treasure trove of personal correspondence, and more than any other documents, their letters- intimate, opinionated, and action-packed- reveal the true nature of their lifelong friendship and creative relationship. Collected here for the first time, they offer an intimate view into the range of artistic vision and complementary sensibilities that fueled the genius of their literary collaborations." --
Includes bibliographical references and index
Keywords: Ferlinghetti, Lawrence / Correspondence; Ginsberg, Allen / 1926-1997 / Correspondence; Ferlinghetti, Lawrence; Ginsberg, Allen / 1926-1997; Ginsberg, Allen -- 1926-1997; Ferlinghetti, Lawrence -- 1919-2021; Geschichte 1900-2000; Poets, American / 20th century / Correspondence; Authors and publishers / United States / Correspondence; Publishers and publishing / United States / Correspondence; LITERARY COLLECTIONS / Letters; Authors and publishers; Poets, American; Publishers and publishing; United States; USA; Briefsammlung -- 1955-1997